Spatiotemporal Coupling Relationship Between Plateau Pika Disturbance and Alpine Meadow Degradation - Zhao Jianyun; Jiang Chuanli; Li Guorong; Gao Chongyue; Wang Zhichao; Wen Lanchong (Shuitu baochi tongbao)
[Objective] Plateau pika (Ochotona curzoniae) is a key species in the alpine meadow ecosystem of the Qinghai-Xizang Plateau. The coupling relationship between pika activity and meadow degradation was analyzed in order to further improve the observation system of plateau pika interference intensity and to provide more comprehensive and scientific investigation data of plateau pika activity. [Methods] An observation and grading system for alpine pika disturbance intensity (PDI) was constructed using observational data from an unmanned aerial vehicle (UAV) and deep learning methods. Spatial-temporal variation analysis was conducted using a landscape index and a coupling degree model to clarify the coupling relationship between pika and meadow degradation. [Results] ①The accuracy of the ResNet-101 model for extracting bald patches on pika mounds reached 92.7%. Slight and light pika disturbance areas accounted for 82.0% of the total area in 2019, and the moderate and high disturbance intensity areas accounted for 62.5% of the total area in 2021. The area with significantly increased PDI from 2019 to 2021 accounted for 43.0% of the total area. ②Alpine meadow vegetation was predominantly classified as moderately degraded in 2019 and 2021. From 2019 to 2021, 30.2% of the area shifted to moderately degraded to severely degraded, and 7.7% of the area experienced a significant decrease in vegetation cover. ③The landscape of the study area transformed to bald patches in a single direction, and the landscape type became more aggregated, regular, and homogenized. The dominance of bald patches in the landscape increased significantly. ④The coupling degree was increased in most regions increased from 2019 to 2021, and the interaction between plateau pika disturbance and alpine meadow degradation was enhanced from 2019 to 2021. [Conclusion] The intensity of plateau pika disturbance in the study area increased from 2019 to 2020, vegetation coverage decreased, and the landscape gradually transformed to bald patches. The alpine meadow degraded under plateau pika disturbance. The coupling effect between plateau pika disturbance and alpine meadow degradation has gradually increased, and it is therefore necessary to take more active prevention and restoration measures.